EFFICIENT MANET- INTERNET INTEGRATION FOR MOBILE DEVICES - tiwari, mahesh kumar; SHANKAR, UDAI; KUMAR, AJAY (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
A mobile ad hoc network (MANET) consists of wireless mobile nodes without having a fixed infrastructure support. The communication between these mobile nodes is carried out without any centralized control. The communication among the nodes within the infrastructure less networks is done through Ad-Hoc routing protocols, But whenever any mobile node want to communicate to a node in a network that is outside the ad hoc network such as internet, there should be an appropriate mechanism for establishing this connection with the internet node or host. Gateway discovery is a fundamental process in connecting MANET with the internet. A mobile node can connect to the internet by discovery of some specialized nodes called as gateway nodes. These Gateway nodes act as a bridge between the mobile ad hoc networks node and the internet. The basic aim of the gateway discovery approach is to modify the route discovery process so that it is not only used for discovery of destination mobile nodes but also the gateways. In this paper we are going to present a review of various gateway discovery approaches which are used for establishing the interconnection of mobile ad hoc networks and internet and going to propose a algorithm that reduce the discovery time of the gateway by selective forwarding and simultaneously also optimize the gateway discovery control overheads.